Ntombi Vimbela! Sexual violence risk reduction intervention: pre and one-year post assessments from a single arm pilot feasibility study among female students in South Africa - Mercilene Tanyaradzwa Machisa; Pinky Mahlangu; Esnat Chirwa; Ncediswa Nunze; Yandisa Sikweyiya; Elizabeth Dartnall; Managa Pillay; Rachel Jewkes (BMC, 2023)
Abstract Background The extremely high prevalence of sexual violence victimisation reported among female students in South African public higher education demands urgent action to develop, rigorously evaluate and scale effective prevention interventions. This article details findings from a pilot feasibility study of Ntombi Vimbela! a campus sexual violence risk reduction intervention developed to tackle the high burden of sexual violence in higher education institutions in South Africa. Methods Ntombi Vimbela! (NV!) is a sexual violence risk reduction intervention that comprises sexuality empowerment, gender and social norm change, early-risk identification, self-defence, resistance and mental wellbeing components. NV! is comprised of ten workshop sessions running for 3.5 h each. Workshops are co-delivered by two trained peer facilitators per group of at most 20 first-year female students. One-year post-intervention quantitative outcome assessments were remotely completed by 98 participants who participated in the NV! pilot workshops. Qualitative assessments were conducted with 35 participants through in-depth telephone interviews (IDTIs). Findings One year after attending NV! workshops, most participants reported improved awareness of sexual rights, assertive communication, shifts in gender equitable beliefs, reductions in rape myth acceptance, improved expressed sexual relationship power sexual decision-making, and improved negotiation within their intimate relationships. Participants' depressive symptoms also significantly decreased. Many participants improved awareness of sexual assault risk and vigilance, including using self-protection strategies such as removing themselves from environments where alcohol intoxication posed sexual assault risks. Some participants used assertive communication to withstand peer pressure to engage in risky sexual behaviours. Most participants scored highly on the self-defence efficacy scale. Some participants were exposed to and successful in using verbal and physical resistance strategies in potential sexual assault risky situations. Conclusion These findings indicate the potential beneficial effects of NV! as a campus sexual violence risk reduction intervention at one-year post-intervention, which must be evaluated in a future rigorous randomised control trial. Pilot trial registered at ClinicalTrials.gov NCT04607564 on 29/10/2020.